Towards sovereign international rela- tions studies? Book review of ‘Liberal values in theory and practice. On the issues of intellectual decolonization of Russia’ by L.S. Voronkov - V. V. Kochetkov (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The book under review is a new monograph by L.S. Voronkov ‘Liberal values in theory and practice. On the issues of intellectual decolonization of Russia’, published in 2024. The reviewer discusses in detail several key topics and central ideas of the book under consideration. The first section covers the author’s views on a set of problems related to the specifics of power relations and the role of political elites in Western liberal democratic states. It also highlights the political and economic contradictions inherent to the liberal democratic model of social development, propagated by the countries of the ‘collective West’ in order to maintain their own dominance in the system of international relations. It is shown that, along with economic and political instruments, Western elites do not disdain practices of cultural hegemony, arising from the colonialism and neocolonialism. The second section considers L.S. Voronkov’s views on the issues of intellectual colonialism. Special attention is paid to the role of Western approaches within the theory of international relations in legitimizing and promoting the interests of the United States and its allies. It is shown that these approaches, positioned as strictly scientific, actually represented a sophisticated system aimed at concealing the real economic interests of Western countries. In this context, the book by L.S. Voronkov is of particular interest since it makes a strong case for the development of Russia’s own perspective on international relations, with due regard to its specific historical features. Although some author’s conclusions and observations can be contested, L.S. Voronkov’s monograph will hopefully contribute to the emergence of Russian sovereign international relations studies.